2018
DOI: 10.1155/2018/4814928
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Lycium barbarum Extracts on UVB‐Induced Damage in Human Retinal Pigment Epithelial Cells Accompanied by Attenuating ROS and DNA Damage

Abstract: The medicinal herb Lycium barbarum fruit has been widely used for improving and maintaining the health of the eyes in the Far East for many centuries. This study is aimed at investigating whether protective effects generated from the aqueous (LBA) and ethanol (LBE) extracts of the L. barbarum fruit existed against oxidative stress-induced apoptosis in human retinal pigment epithelial cells. L. barbarum extracts LBA and LBE exerted the activity of ROS scavenging and rescued UVB irradiation-induced growth inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 60 publications
1
25
0
Order By: Relevance
“…Besides that, the upregulation of cytochrome C protein was also recorded by Balaiya et al [ 112 ], which suggests that the integrity of mitochondrial membranes was compromised. This data agrees with other studies that reported the loss of mitochondrial potential and the number of mitochondria in ARPE-19 and DrRPE cells following exposure to UVB irradiation [ 33 , 103 , 113 ]. Another interesting study displayed vast changes in the mitochondrial morphology and movement before and after UVB irradiation in ARPE-19 cells.…”
Section: Uvb Induced Dysregulation On In Vitro supporting
confidence: 93%
See 2 more Smart Citations
“…Besides that, the upregulation of cytochrome C protein was also recorded by Balaiya et al [ 112 ], which suggests that the integrity of mitochondrial membranes was compromised. This data agrees with other studies that reported the loss of mitochondrial potential and the number of mitochondria in ARPE-19 and DrRPE cells following exposure to UVB irradiation [ 33 , 103 , 113 ]. Another interesting study displayed vast changes in the mitochondrial morphology and movement before and after UVB irradiation in ARPE-19 cells.…”
Section: Uvb Induced Dysregulation On In Vitro supporting
confidence: 93%
“…Many in vitro studies have shown that RPE cells which were irradiated with UVB had displayed increased cell death, DNA fragmentation, and apoptosis [ 98 , 103 , 104 ]. Microscopic images of microvillus shedding, nucleolus degeneration, the formation of vesicular structures, and mitochondrial degradation are the hallmarks of apoptosis that were seen in ARPE-19 cells after UVB irradiation [ 104 ].…”
Section: Uvb Induced Dysregulation On In Vitro mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a study by Hsieh et al has shown that L. barbarum could reduce cellular oxidative stress and protect cells from apoptosis. 74 In addition, it can alleviate inflammation and improve neurotransmission in neurodegenerative diseases, 75 and reduce insulin resistance induced by a high-fat diet. 76 The antioxidative mechanism of L. barbarum may be related to AMPK and Nrf2 pathways.…”
Section: Therapeutic Drugs Targeting Senescencementioning
confidence: 99%
“…The whole plant extract has also shown protection against oxidative and apoptotic effects in cultures of human lens epithelial cells [15,16]. A recent study has shown that the ethanolic extracts of L. barbarum exhibited significant protection on UVB-induced growth arrest of in human retinal pigment epithelial cells (ARPE-19) [17].…”
Section: Introductionmentioning
confidence: 99%